Attitudes of the Faculty Members Towards E-Learning: The Influence of Gender, Years of Experience, Academic Degree, and Academic Discipline - Almutairi, Dhaifallah Obaid (The Arab Journal of Administration, 2025)
This paper reports a study of the attitudes of faculty members at Business School at Imam Mohammed ibn Saud Islamic University towards e-learning. Using a quantitative approach, the study aimed to investigate the influence of the following factors on the attitudes of the faculty members towards e-learning, gender, years of experience, academic degree, and academic discipline. A sample of 49 faculty members participated in the survey. The study results revealed that the faculty members had a highly positive attitude towards e-learning with a score of 3.89 out of 5. In addition, the results showed that there was no statistically significant variation in the behavior of the participants based on the previously mentioned factors (gender, years of experience, academic degree, and academic discipline). The study concluded with several recommendations concerning faculty members such as ongoing training on e-learning, attending academic workshops and conferences on new technologies. Furthermore, as one of the main components of the learning process the University should organize training sessions to raise the awareness of the students regarding e-learning. Moreover, set up future aiming to deal with the expected increasing number of the faculty members, students, and institutes alike; to create a suitable academic e-learning environment. Finally, conduct new studies investigating more factors that possibly impact the e-learning process.